PENGARUH PSYCHOLOGICAL CAPITAL TERHADAP CAREER COMPETENCY YANG DIMEDIASI OLEH CAREER ADAPTABILITY PADA FRONTLINER PERBANKAN DI KOTA BANDA ACEH - Siti Bellia Umairah; Murkhana Murkhana (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
Referring to the Construct Career Theory, this study aims to measure the effect of psychological capital, career competency and career adaptability. The sample used in this study was the State-owned enterprises banking frontliners in the city of Banda Aceh, totaling 225 respondents. The data collection used in this study was a questionnaire. The sampling technique used was purposive sampling. Path analysis is used as a method of analysis to determine the effect of all the variables involved. Based on the results of the Path analysis, it indicates that there is a significant relationship between psychological capital and career adaptability. In addition, career adaptability has a positive impact on career competency. In this connection, career adaptability mediates the relationship between psychological capital and career competency.